Antimicrobial susceptibility of microorganisms isolated from sputum culture of patients with cystic fibrosis: Methicillin-resistant Staphylococcus aureus as a serious concern. (November 2016) - Mazloomi Nobandegani, Narges; Mahmoudi, Shima; Pourakbari, Babak; Hosseinpour Sadeghi, Reihaneh; Najafi Sani, Mehri; Farahmand, Fateme; Motamed, Farzaneh; Nabavizadeh Rafsanjani, Raheleh; Mamishi, Setareh
Abstract: Introduction: Infection is a major cause of morbidity and mortality in patients with cystic fibrosis (CF). Antimicrobial resistance of the bacterial spp. particularly methicillin resistance in Staphylococcus aureus has caused a lot of attention. The aim of this study was to describe the prevalence of S . aureus, Pseudomonas aeruginosa and Burkholderia cepacia- complex as well as their antimicrobial susceptibility patterns in CF patients in an Iranian referral pediatrics Hospital. Material and methods: From March 2011 until February 2012, 172 samples were collected at the Children Medical Center (CMC), an Iranian referral hospital in Tehran, Iran. Sputum specimens were cultured for the following bacterial pathogens: P . aeruginosa, S . aureus, B . cepacia complex. Antimicrobial susceptibility was performed according to the Clinical Laboratory Standards Institute recommendations. Results: In our study, 54% of the patients (n = 93) harbored at least once S . aureus, 30% (n = 52) P . aeruginosa, and 2% (n = 3) Burkholderia cepacia . In 40 patients (23%), none of these organisms was grown. An increasing colonization rate of P . aeruginosa in the second decade of life was found. In contrast, the colonization rate of S . aureus was constant in both decades of life. Methicillin resistant S . aureus (MRSA) was detected in 40 isolates (43%). Among MRSA, no resistance against vancomycin, linezolid and quinupristin/dalfopristin occurred. The susceptibility of P . aeruginosa isolates to meropenem, imipenem, doripenem, levofloxacin and polymixin B were more than 90%. Conclusion: The prevalence of MRSA has been rising. Since its impact on clinical outcomes, optimal prevention and treatment strategies are unclear, further studies to expand the knowledge about the infection control strategies and MRSA treatment are highly recommended. Highlights: In this study, 54% of the CF patients (n = 93) harbored at least once S . aureus, 30% (n = 52) P . aeruginosa, and 2% (n = 3) Burkholderia cepacia . The prevalence of various bacterial species in different age groups showed an increase of the colonization rate for P . aeruginosa in the second decade of life. The colonization rate for S . aureus was constant in both decades of life. Methicillin resistant S . aureus (MRSA) was detected in 40 isolates (43%). Among the MRSA no resistance against vancomycin, linezolid and quinupristin/dalfopristin occurred. The concurrent colonization with P . aeruginosa and S . aureus was higher in patients in the age group of more than 10 years compare to less than 10 years (29% vs. 15%).